Experimental bound entanglement through a Pauli channel - Amselem, Elias (Nature Publishing Group, 2013)
Understanding the characteristics of a quantum systems when affected by noise is one of the biggest challenges for quantum technologies. The general Pauli error channel is an important lossless channel for quantum communication. In this work we consider the effects of a Pauli channel on a pure four-qubit state and simulate the Pauli channel experimentally by studying the action on polarization encoded entangled photons. When the noise channel acting on the photons is correlated, a set spanned by four orthogonal bound entangled states can be generated. We study this interesting case experimentally and demonstrate that products of Bell states can be brought into a bound entangled regime. We find states in the set of bound entangled states which experimentally violate the CHSH inequality while still possessing a positive partial transpose.